2018
DOI: 10.1111/dgd.12562
|View full text |Cite
|
Sign up to set email alerts
|

Endosomal vacuoles of the prepupal salivary glands of Drosophila play an essential role in the metabolic reallocation of iron

Abstract: In the recent past, we demonstrated that a great deal is going on in the salivary glands of Drosophila in the interval after they release their glycoprotein-rich secretory glue during pupariation. The early-to-mid prepupal salivary glands undergo extensive endocytosis with widespread vacuolation of the cytoplasm followed by massive apocrine secretion. Here, we describe additional novel properties of these endosomes. The use of vital pH-sensitive probes provided confirmatory evidence that these endosomes have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 120 publications
(182 reference statements)
0
4
0
Order By: Relevance
“…Farka s et al (2018) have reported that a key function of the basally derived endosomes in the Drosophila prepupal (PP) salivary glands (SGs) is to support iron import via basal endocytosis. This is followed by strong vacuole acidification to increase the activity of ferrireductase, which is required to release bivalent cationic Fe 2+ for its metabolic utilization in the cytosol (Farka s et al, 2018). These authors provided strong supportive evidence for the involvement of the iron-transferrin system in this process (Farka s et al, 2018), which is similar to the known iron-importing endosomal systems in other model organisms (Lambe et al, 2009;Knutson, 2007;McKie, 2005).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Farka s et al (2018) have reported that a key function of the basally derived endosomes in the Drosophila prepupal (PP) salivary glands (SGs) is to support iron import via basal endocytosis. This is followed by strong vacuole acidification to increase the activity of ferrireductase, which is required to release bivalent cationic Fe 2+ for its metabolic utilization in the cytosol (Farka s et al, 2018). These authors provided strong supportive evidence for the involvement of the iron-transferrin system in this process (Farka s et al, 2018), which is similar to the known iron-importing endosomal systems in other model organisms (Lambe et al, 2009;Knutson, 2007;McKie, 2005).…”
Section: Discussionmentioning
confidence: 74%
“…This is followed by strong vacuole acidification to increase the activity of ferrireductase, which is required to release bivalent cationic Fe 2+ for its metabolic utilization in the cytosol (Farka s et al, 2018). These authors provided strong supportive evidence for the involvement of the iron-transferrin system in this process (Farka s et al, 2018), which is similar to the known iron-importing endosomal systems in other model organisms (Lambe et al, 2009;Knutson, 2007;McKie, 2005). D. melanogaster MCO3 was reported to possess multicopper ferroxidase activity (as does hephaestin in mammals) and to possibly be involved in iron homeostasis (Bettedi et al, 2011;Lang et al, 2012;Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the lack of vertebrate transferrin receptor homolog in insects/mosquitoes, it remains unresolved how loading and unloading of iron are achieved at midgut and ovary surfaces, respectively [8,52]. A recent study by Farkas et.al 2018 suggests the involvement of basally derived endosomes in iron import to the target cells is important in the insect D. melanogaster and proposes that basal endocytosis is followed by vacuole acidification, a process leading to the activation of ferrireductase for iron release and metabolic utilization [53]. Several studies highlight that transferrin plays an antibacterial immune role against microbial infection in insects [54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…To detect chitin (a major component of taenidia) in fi xed tissue, SGs (or tracheae) were stained with Calcofl uor White M2R (also known as Fluorescence Brightener 28, FB28; Sigma, # F-3543) at pH 9 in 0.2 M Tris buffer containing 0.1% Triton X-100 (Serva) for 2-3 h at room temperature. Whenever necessary, samples were also counterstained with Alexa Fluor 488 or Alexa Fluor 546 phalloidin (Molecular Probes/Invitrogen) to detect fi lamentous actin, as previously described (Farkaš et al, 2015(Farkaš et al, , 2018.…”
Section: Immunohistochemistry and Confocal Microscopymentioning
confidence: 99%